„Tak działa nauka”. Retoryczne aspekty naukowego marketingu - Pawinski, Paweł (2022)
The article is an attempt to analyse the rhetorical ways of constructing the scientific qualities of three publications in the field of marketing communication: Scientific Advertising from 1923 (author: Claude C. Hopkins), 22 Immutable Laws of Marketing from 1994 (authors: Al Ries and Jack Trout), and How Brands Grow from 2010 (author: Byron Sharp). Scientific qualities of the general approach and specific findings are built primarily on the basis of the concept of marketing laws: exact, universal and unchanging principles/patterns (as reconstructed in the chapter What are the laws of marketing?), derived from a wide range of data and appropriate methodological procedures (What should marketing be based on?), ensuring business effectiveness for market entities (What are the effects of relying on the laws of marketing?). Authors define their perspective in opposition to the lack of empirical grounding of marketing principles and false premises they are derived from (What shouldn’t marketing be?). The approaches presenting marketing as a science are thus opposed to the alternative approaches, which are describing marketing (and in particular: advertising and the process of its creation) as an art.
Keywords: scientific rhetoric; marketing science; marketing art; marketing communication; advertising; laws of marketing; image of marketing